Neuroimaging in Iran: A Review - G. Ali Hossein-Zadeh; Hamid Soltanian-Zadeh (Basic and Clinical Neuroscience, 2010)
ABSTRACTNeuroimaging allows noninvasive evaluation of the anatomy, physiology, and function of the brain. It is widely used for diagnosis, treatment planning, and treatment evaluation of neurological disorders as well as understanding functions of the brain in health and disease. Neuroimaging modalities include X-ray computed tomography (CT), magnetic resonance imaging (MRI), single photon emission computed tomography (SPECT), positron emission tomography (PET), electroencephalography (EEG), and magnetoencephalography (MEG). This paper presents an overview of the neuroimaging research in Iran in recent years, partitioned into three categories: anatomical imaging; anatomical image analysis; and functional imaging and analysis. Published papers reflect considerable progress in development of neuroimaging infrastructure, hardware installation and software development. However, group work and research collaborations among engineers, scientists, and clinicians need significant enhancement to optimize utility of the resources and maximize productivity. This is a challenge that cannot be solved without specific plans, policies, and funding.